English teaching profiles at islamic Of elementary schools in kuranji - padang - Rasmita Rasmita (Jurnal Ilmiah Pendidikan Scholastic, 2018)
The design of this research was descriptive qualitative that to draw about English teaching profiles at Islamic of Elementary Schools in Kuranji – Padang. The researcher takes three schools by using purposive sample. They were Islamic State of Elementary schools Korong Gadang, Islamic State of Elementary School Gunung Sarik and Private Islamic State of Elementary School Sungai Sapih. The respondents consisted of three English teachers and the headmasters. In gathering the data, the researcher did observation and interview as instruments. In analyzing the data, the resercher followed two ways, namely; pure analysis and analytic. Pure analysis and analytic in order to describe the data naturally and connect it to the theory. The findings of this research showed that the English teachers at Elementary School should graduate from English pedagogical, because of that the teacher have to good techniques in teaching. In spite of the English teachers must able to prepare the suitable media with the material. The English teachers also use good methods and evaluation to increase the students’ achievement.